AFISSULA PRONOTONIGERATUS (COLEOPTERA : COCCINELLIDAE), A NEW SPECIES FROM INDIA - SINGH, TARLOK; SINGH, VIJAY KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1998)
Afissula pronotonigeratus sp. n, described from India, G. assula has been raised by Kapur (1958), and only four species of the same are known from India so far. The present one is an addition to the existing record. A significant contribution towards the taxonomy of this genus has been made by Kapur (1958 & 1963) and Miyatake 1967 & 1985).